Brainatomy—Demystifying the Temporal Bone, Rule of 3-2-1. Issue 2 (February 2022) - Er, Kadir; Patsalis, Dimitrios; Katsigiannis, Sotirios; Schmieder, Kirsten; Baskaya, Mustafa K.; Gierthmuehlen, Mortimer
Abstract : BACKGROUND: The temporal bone is difficult to comprehend in three-dimensional (3D) space. We provide a novel 3D mental model of the temporal bone which helps clinicians and surgeons dealing with it in teaching, diagnosing, conservative managements, and preoperative and intraoperative orientation. This study is part of the scientific project Brainatomy. OBJECTIVE: To analyze and simplify the temporal bone anatomy to enhance its comprehension and long-term retention. METHODS: The study was conducted at the Neurosurgical Department of the University Hospital of Bochum, Germany. We retrospectively analyzed data sets of 221 adult patients who underwent computed tomography (CT) of the skull (n = 167) and magnetic resonance imaging (MRI) of the brain (n = 54). A total of 142 patients with their respective imaging scans remained in our pool of interest after excluding 79 scans. The raw digital imaging and communications in medicine scans were transformed into 3D objects. Spatial analyses were then conducted, and all collected data were used to create our own 3D model of the temporal bone. RESULTS: We define the temporal bone as a prism-shaped model and divide it into 6 compartments: apex, neurovascular, mastoid, blank, tympanic, and temporomandibular compartments. The division into compartments has been achieved with the "Rule of 3-2-1." Finally, the 3D model has been used to record a video (Video), using a novel and "easy-to-follow" didactic approach. CONCLUSION: This simplified 3D model along with the corresponding video (Video) potentially enhances the efficiency of studying temporal none anatomy with a novel "easy-to-follow" approach.